Phylogenetic comparison of I-antigens protein as potential candidate for diagnostic and vaccine for Cryptocaryon irritans parasite - Adura, Mohd Adnan (Universiti Kebangsaan Malaysia, 2016)
The fish parasite C. irritans i-antigen protein has high potential to be developed as a commercial vaccine against C. irritans. However, variation within the i-antigens of different C. irritans serotypes affected the cross-protection provided towards different isolates of C. irritans when the i-antigen was evaluated as a candidate vaccine. This study was conducted to compare the sequences of various C. irritans i-antigens isolated in Malaysia with i-antigen sequences of previously reported C. irritans isolates. Phylogenetic comparison was performed to predict the protein’s potential to be developed as a screening marker and vaccine candidate against various C. irritans isolates. Multiple sequence alignment of i-antigen amino acid sequences was undertaken using ClustalX and phylogenetic analysis of i-antigen was performed using the maximum parsimony (MP) and Bayesian methods. Nine C. irritans unique transcripts (UTs) had significant matches with i-antigen sequences in the NCBI protein database, with similarities ranging between 41 and 71%. Both MP and Bayesian trees generated showed that i-antigens cn56 and cn57 variants clustered together in one group while other i-antigen variants were divided over two different groups and the grouping was supported by the presence of conserved amino acids in their respective groups. Further research should identify variants of the i-antigen suitable for serodiagnostic candidates and provision of cross-protection against multiple strains of C. irritans globally